MEDIATING EFFECT OF TALENT MANAGEMENT ON THE RELATIONSHIP BETWEEN TOTAL QUALITY MANAGEMENT, ENTREPRENEURIAL ORIENTATION, ORGANIZATIONAL EXCELLENCE, AND ORGANIZATIONAL PERFORMANCE IN DUBAI POLICE - Saleh Almazrouei; Norziani Dahalan (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Both public and private organizations are facing various challenges in the current environment due to range of complexities as exists in the market. However, to achieve higher organizational performance, more attention is required towards different tangible and intangible organizational resources along with strategic capabilities. The purpose of this study is to examine the role of total quality management, entrepreneurial orientation, organizational excellence towards organizational performance from the context of Dubai Police. Additionally, it also explores the mediating effect of talent management on the relationship between total quality management, entrepreneurial orientation, organizational excellence, and organizational performance. A sample of 453 valid responses through online survey questionnaire was collected and analzyed. More specifically, descriptive statistics, correlational and demographic analyses and both measurement model and structural model was assessed. The study findings through measurement model confirm the reliability, validity, internal consistency, and discriminant validity of the latent constructs. Finally, the findings through PLS-SEM approach confirms that direct and significant relationship between total quality management, entrepreneurial orientation, organizational excellence, and organizational performance, respectively. The testing of mediating effect confirms that talent management significantly mediates the relationship between TQM-OP, between EO-OP, and between OE-OP, accordingly. The study findings would be of great support to various policy makers specifically in the Dubai Police.